Impact of Butterfly Pea (Clitoria ternatea) Extract Levels on the Physical, Sensory, and Antioxidant Activity of Pasteurized Milk - Ismanto, Arif; Kinasih, Dewi Sekar; Haris, Muh. Ichsan; Indana, Khoiru; Anindyasari, Dinar (CV. Komunitas Dunia Peternakan, 2025)
The addition of butterfly pea (Clitoria ternatea) extract which contains antioxidants into pasteurized milk is expected to increase the intake of antioxidants in the body. This research was conducted to evaluate the effect on pH, color, organoleptic chracteristic, and antioxidant activity of pasteurized milk. This study used a completely randomized design (CRD) with 5 treatments and 4 replications. The results of this study showed that increasing concentration of extract decreased pH, brightness, redness and yellowness. P3 was the most preferred treatment according to sensory evaluation. The antioxidant activity increased proportionally with extract concentration, reflected in decreasing IC50 values from 116.54 ppm (P0) to 19.06 ppm (P4). These findings indicate that the enrichment of pasteurized milk with butterfly pea extract effectively enhances its antioxidant capability while maintaining favorable sensory properties, particularly at moderate extract concentrations.